Life cycle Cost of Standalone Solar Photovoltaic System Powering Evaporative Cooler and Heat Pump Water Heater for Australian Remote Homes. (June 2016) - Abdullah, Gazinga F.; Saman, Wasim; Whaley, David; Belusko, Martin
Abstract: Deploying standalone solar air-conditioning systems in residential buildings forms a radical demand-side energy management solution for eliminating the peak electricity demand from residential air-conditioning. For existing grids to meet this demand a correspondingly major investment is required to extend the capacity of the infrastructure. For any standalone solar air-conditioner to become acceptable to individual residents, it needs to be cost competitive with buying electricity from the grid. For dry climate regions such as South Australia, evaporative coolers (EVAP-C) can handle the building space cooling load sufficiently and require only small amounts of power to operate. Thus, the need here is for a small capacity standalone photovoltaic system (SPVS), and corresponding less investment. Since evaporative coolers switch off in winter and SPVSs have massive excess power, a significant amount of the SPVS's power is dumped. To augment the SPVS's economic feasibility with a little oversizing, the SPVSs can also power a domestic heat-pump water heater (HP-WH) throughout the year, which in return benefits householders by obviating the need to purchase hot-water heating energy. This study, aims to techno-economically optimize the size of the components comprising an SPVS powering EVAP-C and HP-WH to meet the demand of a typical Australian house model, and for two widely different climates. The study was performed with modelling and simulation using TRNSYS then coupled with GenOpt to carry out system optimization. A comprehensive economic evaluation of the most optimized system size revealed that, for an on-grid house, taking into account current purchase costs of components and cost of power in Australia, even for a low energy consumption air-conditioner such as an EVAP-C, even when coupled with HP-WH, a SPVS is still not cost competitive to the cost of purchased the same amount of power from the grid. However, for future off-grid houses, not presently, wherever SPVS's are up taken, they will obviate the equivalent resulting charges for augmenting the capacity of the grid infrastructure. Optimized SPVSs have the potential to become gradually grid cost competitive while electricity prices continue to rise and component costs drop. How soon this will occur, depends on the electricity price inflation rate in Australia, our economic evaluation has forecasted this to be around the twenty year mark.